INTUISI SEBAGAI SALAH SATU SOLUSI MERAIH PRESTASI BELAJAR MATEMATIKA - Sa'o, Sofia (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2020)
Mathematical problems are often solved without using conventional methods but using intuition thinking. Intuitive thinking is a cognitive process that leads to ideas as strategies for making decisions that produce spontaneous answers in solving problems. Spontaneous answers are written and spoken expressions that help a person solve math problems without using analytical thinking. This study aims to describe the various forms of intuition that arise when students solve math problems. The research method used is descriptive qualitative method to describe students' intuitive thinking processes through test instruments and interviews. The results showed that the form of intuitive thinking that emerged was (1) affirmatory intuition, namely direct cognition to understand the problem and (2) perceptual and global components, because students made perceptions of the answer solutions to be generated, then resolved until they got the results. In addition, it was also found that intuitive thinking that is raised as a strategy in making decisions is based on feelings, intrinsics and interventions to produce answers to solving the problems faced